2018
DOI: 10.1177/1524839918781527
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness of Low-Risk Alcohol Use Guidelines

Abstract: A provincial public health education campaign was effective at increasing awareness of the LRDG, though uptake was lowest among those at highest risk for heavy drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Other studies, mainly cross-sectional in nature, have shown improved knowledge of LTH associated with alcohol and of LRDG in drinkers exposed to similar prevention campaigns [10,21,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies, mainly cross-sectional in nature, have shown improved knowledge of LTH associated with alcohol and of LRDG in drinkers exposed to similar prevention campaigns [10,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…An exposure to the Ravages campaign may have increased risk perception among women and then affected their behavioural intentions. The effectiveness of campaigns may also vary by age and social background [21,27,28]. With regard to socio-economic level, the information disseminated in prevention campaigns may be minimized [29,30] depending on the individual's cultural and social background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies assessing the level of knowledge of young people about the health effects of alcohol. The available literature which analysed respondents’ knowledge of alcohol focused on specific aspects, such as the energy value of alcoholic beverages [ 141 ], knowledge of the term “standard drink” [ 142 , 143 , 144 ] or their impact on health [ 30 , 145 ] and foetal development [ 146 ]. However, there are no studies that assess all these aspects in a single questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…And finally, McNally's "Should I Have Another?" campaign on alcohol awareness, which details precampaign and post campaign data on drinking as well as the measures taken for the awareness campaign [8].…”
Section: Literature Reviewmentioning
confidence: 99%